Pozycja kobiet na polskim rynku pracy. Uwarunkowania prawne i rzeczywistość - Kałążna, Klaudia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Polish women are in a significantly less advantageous position than men with respect to employment, or professional promotion. They are also the majority among the unemployed, despite their increasingly better education. The unequal attitude to women is also expressed in terms of their salaries – on average women earn 17% less than men. The paper presents the statistical data on women’s unemployment, describes the legal conditions of women’s functioning on the labor market, and shows that, despite the formal ban on discrimination, it is present in more or less concealed forms. The paper describes the obstacles women face trying to find employment and in taking full advantage of their skills, e.g. the glass ceiling. The author familiarizes the notion of the glass ceiling and she also refers to the role of stereotypes and the atmosphere of one’s home in the future functioning on the labor market.